Business Feasibility Aspects of Village-Owned Enterprises in Indonesia - Darmawan, Darmawan (JESI (Jurnal Ekonomi Syariah Indonesia), 2022)
This research is the first in an effort to find out the Business Feasibility Aspects of Village-Owned Enterprises (BUM Desa) in Indonesia. This research is very important because the Village Fund of IDR 329 trillion over the last five years has not been able to be maximally utilized by BUM Desa. There are 2,188 BUM Desa not operating and 1,670 BUM Desa that are running but have not yet contributed optimally to driving the village economy. BUM Desa must be revitalized, improving the performance of BUM Desa is important and urgent because Village Funds continue to increase every year. In 2020, the government allocates a budget of IDR 72 trillion. This study seeks the Business Feasibility Aspects of Village-Owned Enterprises (BUM Desa) by using questionnaires and direct field observations throughout Indonesia with a sample expected to represent Java and Outside Java. It was found that there are five aspects that can measure the feasibility of a business in the BUM Desa business unit: Market and Marketing Aspects; Management and Human Resources Aspects; Financial aspect; Business Environment Aspect; and Legal Aspects. The main problem of BUM Desa is in the financial aspect (76,56%) and the aspect of the business environment (73,29%). Meanwhile, the Market and Marketing Aspects; Management and HR Aspects; Legal Aspect  have a feasibility score of above 80%. The business feasibility of BUM Desa in Java is better than outside Java. The social and financial business type has a lower feasibility level than other types of business.